2012
DOI: 10.1016/j.jvs.2011.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes after infolding or collapse of thoracic stent grafts

Abstract: TAG device infolding appears to be an infrequent event, primarily occurring in young trauma patients secondary to excessive oversizing and severe proximal aortic angulation. However, there clearly exists a need for devices that treat such patients. As a result, future device designs should consider the compression failure mode when being designed in order to help prevent such events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 16 publications
1
72
0
Order By: Relevance
“…299 TEVAR may result in stent graft related complications such as endoleak, stent graft migration, or stent graft collapse. 106,107 The primary importance of the surveillance protocols is to prevent these complications.…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…299 TEVAR may result in stent graft related complications such as endoleak, stent graft migration, or stent graft collapse. 106,107 The primary importance of the surveillance protocols is to prevent these complications.…”
Section: Surveillancementioning
confidence: 99%
“…Other complications (device or procedure related) can include aortic rupture during deployment, angulation, migration, or collapse of the stent graft, false aneurysm formation at the proximal or distal end of the stent graft, graft erosion, or stent frame fracture. 106 A retrograde type A dissection is associated with devastating outcomes. TEVAR for aortic dissection is particularly prone to retrograde type A aortic dissection.…”
mentioning
confidence: 99%
“…Oversizing can potentially result in infolding or wrinkling of the device and under sizing can definitely lead to endoleaks [4] even after balloon touch-up. In addition, size discrepancies can lead to distal ischemia caused by stenosis or occlusion of the device lumen [5].…”
Section: Discussionmentioning
confidence: 99%
“…TEVAR for traumatic injuries is effective but its outcome remains a concern especially in young patients [4,5]. In these individuals, the endograft is often implanted "off-label", and device oversizing is essential for fixation at the level of the proximal landing zone [6]. This may ultimately induce to premature device failure and endograft collapse/ infolding, which usually requires a secondary intervention by means of re-do TEVAR or conversion to open surgery with attendant high morbidity and mortality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rates of endograft collapse after TEVAR for traumatic injuries are not well defined [8,11], although collapses usually present in the early post-operative period (median time of 15 days) [12]. It has been recently reported that the Gore TAG thoracic endoprosthesis (W. L. Gore and Assoc, Flagstaff, Ariz) accumulated a 0.4% frequency rate of device collapse among 33,000 endografts distributed worldwide [6]. However, collapse rates likely differ for other available endografts.…”
Section: Introductionmentioning
confidence: 99%